Student and Teacher Responses to the Use of Media and Teaching Tools in the STEM Boardgame - Nur Hasanah; Erna Suhartini; Tri Wahyuningsih; Yana Supriyatna (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to determine the responses of students and teachers to the use of media and teaching tools in the STEM Boardgame, an integrated learning tool that combines board games, teaching modules, and worksheets in STEM learning in elementary schools. Methodology: The study used a quantitative descriptive survey design. The subjects consisted of 27 fifth-grade students and one teacher, selected using purposive sampling based on their direct involvement in learning. Data were collected using a Likert-scale questionnaire with 38 items for students and 39 for teachers, each covering aspects of game and teaching devices. The student instrument was tested for reliability, yielding a Cronbach’s Alpha of 0.924. Data were analyzed using quantitative descriptive methods. Main Findings: Students' responses to the game device aspect reached 83.04% (Very Good) and the teaching device aspect 80.93% (Very Good), with an overall average of 81.99% (Very Good). Teacher responses to the game device aspect reached 92.19% (Very Good) and the teaching device aspect 79.35% (Good), with an average of 85.77% (Very Good). Teachers placed greater emphasis on the board-game aspect, while students rated the teaching-device aspect higher. Novelty/Originality of this study: This study specifically evaluates user responses to integrated STEM learning tools that encompass two aspects simultaneously-the game tool (board game) and the teaching tool from two direct user perspectives. Unlike previous studies, which generally examine only one aspect at a time, this study provides a more comprehensive empirical picture.